VALIDITAS MEDIA PEMBELAJARAN KONKRET SMARTCOUNT BERBENTUK BATANG WARNA DALAM KETERAMPILAN BERHITUNG SISWA KELAS II SD - Yunita Nor Hidayah; Azahro Isna Mubarok; Lukman Hanif Ilham F; Siti Masfuah; roslita anggraeni (Alpen: Jurnal Pendidikan Dasar, 2026)
Abstract : This study aims to develop and test the feasibility of concrete learning media “Smartcount” in the form of color bars in improving the counting skills of grade II elementary school students. The study used a research and development (R&D) approach with a modified ADDIE model until the initial implementation stage. A validation instrument was developed to assess the content, visual, and functionality aspects, involving two validators (material and media experts). The validation results showed that the Smartcount media obtained an average score of 4.54, which fell into the “very feasible” category. This finding shows that Smartcount media is effective as a visual-based counting learning tool that is fun and in accordance with the characteristics of early childhood students. Keyword : concrete media, counting skills, media development, Smartcount, elementary school student.